Prevalence of Brucellosis in cattle, sheep, and goats in rural pastoral settings in Northern Tanzania - Sharadhuli I. Kimera; Lesakit S.B. Mellau; John B. Kaneene (One Health)
A study was designed and carried out between January and June 2016 as part of a larger initiative to assess the health status of animals in a pastoral village of Naitolia, Monduli District in northern Tanzania. A total of 511 blood samples from 239 cattle, 207 goats, and 65 sheep were collected and analyzed for the presence of haemoparasites causing tick-borne diseases and Brucella spp causing brucellosis in animals and humans. The serum obtained from the blood was tested using a Rose Bengal Plate test for Brucella where cattle had overall 4 positives (1.7 %) and in sheep and goats 12 were positive (4.41 %). Among the sheep and goats, the goats had 11 positives (5.31 %) and only one sheep (1.54 %) was positive for Brucella spp. There was no statistically significant difference with age, sub-village, lactation status and species, however, the Ormang'wai sub-village had a 25 % less chance of seroconversion, and lactating animals had 18 % more odds for seropositivity. On the other hand, goats had more than triple the chance of seroconversion. These findings indicate that herds in pastoral settings are exposed to infections and potentially pose a risk to communities, especially women and children who attend to the animals most of the time. We recommend incorporating food safety education as part of one health intervention to improve rural livelihoods and welfare.